Distribusi Spasial Padang Lamun di Pesisir Kecamatan Pemenang, Lombok Utara - Salsabila, Baiq Annisya; Farista, Baiq; Sukenti, Kurniasih; Virgota, Arben (Biocaster : Jurnal Kajian Biologi, 2025)
The distribution of seagrass ecosystems along the coast of Pemenang District, North Lombok Regency, plays an important ecological and economic role. However, this ecosystem is vulnerable to damage due to human activities. The purpose of this study was to analyze the spatial distribution and extent of seagrass cover based on its cover density level. This study used remote sensing methods through the interpretation of Sentinel-2A images. The analysis process included image merging, image cropping, water column correction using the Lyzenga algorithm, image classification using supervised and unsupervised methods, and field validation at 60 observation points. The results showed that seagrass meadows were widespread along the coast and Gili islands (Gili Trawangan, Gili Meno, and Gili Air), with a total area of ​​685.26 ha. Seagrass cover density was classified into three categories, namely high (33.69%), medium (45.02%), and low (21.29%), with a mapping accuracy level of 73.33%. Based on the Decree of the Minister of Environment No. 200 of 2004, most seagrass meadows were categorized as damaged. Factors influencing this condition include domestic waste, tourism activities, ship anchors, human movement (madak), and turtle grazing activity. Seven seagrass species were identified, with Cymodocea rotundata being the most dominant. These findings emphasize the importance of regular monitoring and ongoing management to maintain the sustainability of seagrass ecosystems in the Pemenang coastal area.